ANALISIS KERAGAAN EKONOMI USAHA PENANGKAPAN IKAN KAPAL MOTOR DI TANJUNG LUAR, LOMBOK TIMUR - Hulaifi Hulaifi (LPPM Universitas Terbuka, 2018)
Economic diversity is a detailed description of fishery business that conducted by an individual or business entity to get some profit by analyzing economically and financially as well as the stability of fishing effort against natural risks and the dynamics of economic also technical change of business. The purpose of this research is to analyze the economic diversity of fishing effort by fisherman who using motor boats in Tanjung Luar, East Lombok, West Nusa Tenggara. The data analysis conducted in the form of analysis economic diversity of fishing business using motor boats. The parameters of economic analysis of the fishing effort business using 3 main criteria and 2 additional criteria. The 3 main criteria are Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit/Cost Ratio (NB/CR). While 2 additional criteria are Payback Period (PP), and Profitability Ratio (PR). The result of this research is fishing business based on the result of economic diversity criteria such as (NPV, IRR, Net B / C Ratio, Profitability Ratio and Payback Period) and the financing sensitivity of fishing vessels by boat is still feasible to be developed, then to obtain optimal benefits the fishermen are expected to increase the size of boats, technology, professional human resources and the addition of machine power used, so that fishermen can operate properly in the waters ZEE is further and deeper. The recommendation from the above fishing effort also need support from other aspect such as legality aspect, fishery fish farming, technical policy from local government and optimum condition at various allocations. Keragaan ekonomi merupakan suatu gambaran secara detail usaha perikanan, yang dilakukan oleh perorangan atau badan usaha untuk mencari keuntungan, dengan menganalisis secara ekonomi dan finansial, serta kestabilan usaha penangkapan ikan tersebut terhadap risiko alam dan kedinamisan perubahan ekonomi dan teknis usaha. Tujuan dari penelitian ini yakni menganalisis keragaan ekonomi usaha penangkapan ikan oleh nelayan kapal motor Tanjung Luar Kabupaten Lombok Timur. Analisis data yang dilakukan berupa analisis keragaan ekonomi usaha penangkapan ikan pada kapal motor. Parameter analisis keragaan ekonomi usaha penangkapan ikan menggunakan 3 kriteria utama dan 2 kriteria tambahan, ketiga kriteria utama investasi tersebut adalah Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit/Cost Ratio (N B/C R), sedangkan 2 kriteria tambahan adalah Payback Period (PP) dan Profitability Ratio (PR). Hasil dari penelitian ini yakni usaha penangkapan ikan berdasarkan hasil kriteria keragaan ekonomi seperti (NPV, IRR, net B/C ratio, profitability ratio dan payback period) dan sensitivitas usaha secara finansial, usaha penangkapan ikan oleh nelayan kapal motor masih layak dikembangkan, dan untuk mendapatkan keuntungan yang optimal, maka nelayan diharapkan untuk menambah ukuran kapal, teknologi, SDM yang profesional dan penambahan kekuatan mesin yang dipergunakan, agar nelayan dapat beroperasi dengan layak di perairan ZEE yang lebih jauh dan lebih dalam. Rekomendasi dari kegiatan upaya penangkapan tersebut di atas, perlu dukungan dari aspek lainnya seperti aspek legalitas, tataniaga ikan yang menguntungkan nelayan, kebijakan teknis dari pemerintah setempat serta tercapainya kondisi optimum pada berbagai alokasi.